Layanan Informasi Perdesaan Berbasis Media Sosial - Tuloli, Mohamad Syafri; Mulyanto, Arip; Novian, Dian (Univeristas Negeri Gorontalo, 2019)
The Covid-19 pandemic that is currently spreading globally has made information and communication technology (ICT) services a basic necessity in our daily activity. With the opening of internet access in villages, it opens up opportunities to maximize ICT's role in improving rural information services. Many of the development of ICT-based services is in the form of a website or mobile application with various interfaces and interactions. This requires training and habituation in the community. This is not easy because these applications are not applications that are used daily. The high use of social media in the community can be used as a forum for providing rural information services. By using social media (chat), services can be created that have advantages over other approaches. Such as: do not require new installations, are intrusive so that information comes directly to users, and does not require much training because they use social media applications familiar to the community. On the other hand, village officials can use services for accessing information services and as a medium for disseminating information needed by the community. A training program and assistance for rural information services based on social media have been carried out in Buloila village. The implementation results show that the program is urgently needed, mainly because the village does not have a rural information service. The social media-based service system's evaluation shows that service users (community, village government, and other parties) feel that the system is feasible to use. Feeling that the system can be learned quickly, is easy to use has well-integrated features. It is just that users feel they need to familiarize themselves with using the service because of the form of interaction that users may never have faced before